Identification, cloning and characterization of an aldo-keto reductase from Trypanosoma cruzi with quinone oxido-reductase activity - Garavaglia, Patricia Andrea (2010)
Drugs currently used for treatment of Trypanosoma cruzi infection, the ethiological agent of Chagas’ disease, have shown side effects and variable efficiency. With the aim to describe parasite enzymes involved in the mechanisms of action of trypanocidal drugs and since it has been reported that reductases are crucial in their metabolism, we attempted to identify novel NADPH-dependent oxido-reductases from T. cruzi. The percolation of a soluble fraction of epimastigote lysates through a Cibacron BlueSepharose column followed by elution by NADPH yielded a predominant protein with an apparent molecular weight of 32 kDa. This protein was identified by MALDI-TOF as an aldo-keto reductase (AKR) and hence denominated TcAKR. TcAKR was mainly localized in the cytosol and was also present in trypomastigote and amastigote lysates. The recombinant TcAKR (recTcAKR) showed NADPH-dependent reductase activity with the AKR substrates 4-nitrobenzaldehyde and 2-dihydroxyacetone. The saturation curves for both substrates were consistent with the Michaelis–Menten model. We also tested whether recTcAKR may reduce naphthoquinones (NQ), since many of these compounds have displayed important trypanocidal activity. recTcAKR reduced o-NQ (1,2-naphthoquinone, 9,10-phenanthrenquinone and -lapachone) with concomitant generation of free radicals but did not exhibit affinity for p-NQ (5-hydroxy-1,4-naphthoquinone, 2-hydroxy-1,4-naphthoquinone, -lapachone and menadione). The substrate saturation curve with o-NQ fitted to a sigmoidal curve, suggesting that recTcAKR presents a cooperative behavior. In addition, three peaks assigned to monomers, dimers and tetramers were obtained when recTcAKR was submitted to a Superose 12 gel chromatography column. TcAKR is the first member of the AKR family described in T. cruzi. Our results indicate that this enzyme may participate in the mechanisms of action of trypanocidal drugs.